Design Thinking as an Effort to Enhance Critical Thinking and Science Literacy in Chemistry Learning: A Systematic Review - Syaza Syahana; Suyanta Suyanta; Dwiani Ratna Sari; Lisya Asmiati; Elma Pujiana (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking skills and science literacy represent two pivotal aspects within education, seeking to cultivate students into knowledgeable, analytical individuals proficient in critical thinking when confronting diverse challenges and life circumstances. In the pursuit of enhancing critical thinking abilities, four fundamental aspects come into play, encompassing the capacity for problem-solving, decision-making, assumption analysis, as well as evaluation and inquiry skills. On the other hand, the literacy aspect comprises the articulation of phenomena through the application of chemical concepts, the resolution of problems through the utilization of chemical comprehension, and the critical analysis of strategies and benefits derived from chemistry education. The primary objective of this study are to analyze research trends on the influence of design thinking strategies in improving students' critical thinking and literacy skills through bibliometric analysis and to ascertain the impact of design thinking strategies on the augmentation of students' critical thinking skills and literacy.  The data sources used came from reputable journals from 2017-2023. The data obtained is secondary data analyzed with VOSviewer on research trends in critical thinking skills and scientific literacy, the number of publications, the type of research, and the samples used. The data analysis technique employed is Miles and Huberman's method, which consists of four stages: data collection, data reduction, data display, and conclusion drawing. The findings of this research indicate that the utilization of design thinking strategies exerts a significant influence on students' critical thinking skills and literacy, employing 13 aspects applicable during the implementation of chemistry learning processes